Sodium found in processed cow milk and estimated intake by infants - Alex Oliveira da Camara; Lucia Gomes Rodrigues; Thaís da Silva Ferreira; Orlando Marino Gadas de Moraes (Jornal de Pediatria, 2021)
Objective: To determine the sodium concentration in cow milk available for sale and to estimate its consumption by infants up to 6 months of age. Methods: Sodium level was determined by flame emission spectrophotometry in eight different lots of five brands of liquid ultra-high temperature milk and three brands of powdered milk. To estimate sodium consumption via cow milk, orientations for exceptional situations when neither breastfeeding nor infant formula is possible were considered. Inferential statistics were performed and results were compared with critical parameters at a 5% significance level. Results: The mean sodium content per portion found in liquid milk (162.5 ± 16.2) mg/200 mL was higher than that in powdered milk (116.8 ± 3.0) mg/26 g. Estimated sodium consumption by infants through powdered milk varied from 149.8 to 224.7% of adequate intake, and via liquid milk can be more than 500% of the adequate intake, reaching 812.4% of it if dilution is not applied. Seven of the eight brands of milk studied had declared, on their labels, that the sodium content was 13–30% lower than that found in chemical analysis. Conclusion: Liquid and powdered whole cow milk have high sodium content, and the content per portion is higher in liquid milk than in powdered milk. The estimated consumption of sodium through these products can far exceed the adequate intake for infants from 0 to 6 months old, even when the recommended dilution and maximum daily volumes are followed.